Diagnosis by metagenomic next-generation sequencing of invasive pulmonary aspergillosis in an infant with chronic granulomatous disease. (2023) - Yang, Aimei; Wang, Chun; Chen, Peiling; Zheng, Guilang; Zhao, Zhenjun; Liu, Jian; Zhang, Jingwen; Wang, Jing; Sun, Yueyu; Yang, Juhua; Guo, Yuxiong
Abstract: Invasive pulmonary aspergillosis (IPA) is a serious fungal infection, with a high degree of mortality in immunocompromised individuals. Diagnosis of IPA is challenging in that clinical manifestations are not specific, with sensitivity of traditional detection procedures low. We report a case of IPA in a chronic granulomatous disease (CGD) infant who was initially suspected to have a lung tumor. Aspergillus fumigatus was identified as the pathogen in bronchoalveolar lavage fluid (BALF) by next-generation sequencing (mNGS). The patient recovered rapidly following a change of appropriate antifungal treatment and was discharged. This case highlights the additional value of BALF-mNGS for the diagnosis of pediatric invasive pulmonary fungal infection in immune-deficient children.